2002
DOI: 10.1897/1551-5028(2002)021<1015:hgagbb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Herring Gulls and Great Black-Backed Gulls as Indicators of Contaminants in Bald Eagles in Lake Ontario, Canada

Abstract: In 2000, a pair of bald eagles (Haliaeetus leucocephalus) nested successfully along the shorelines of Lake Ontario in North America for the first time since 1957. However, it is a continuing question whether bald eagles will be able to reproduce successfully as they return to nest on Lake Ontario. Great black-backed gulls (Larus marinus) and herring gulls (L. argentatus) were selected as surrogate species to predict contaminant levels in eggs of bald eagles nesting on Lake Ontario. Because of the suspected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In 1975, White and Cromartie (1977) analyzed 18 red-breasted merganser eggs from the same area in Lake Michigan as we collected from; the mean concentration of PCBs was 45 μg/g, compared to 21 μg/g in our 1977-1978 collection, 8.5 μg/g in our 1990 collection, and 4.6 μg/g in our 2002 collection. The White and Cromartie (1977) means were arithmetic means, but according to White (personal communication) the arithmetic and geometric means were very Table 1 Comparison of organochlorine pesticides and PCBs (μg/g, wet-weight; n = 12) in red-breasted merganser eggs collected in 1977-1978, 1990, and 2002from Lake Michigan 1977-197819902002 PCBs 21 a (10-34) b A 8.5 (4.0-14) B 4.6 (1.8-13) C p, p -DDE 6.5 (3.3-11) A 2. 2 (1.1-3.3 Faber and Hickey (1973), and the 1975 data came from White and Cromartie (1977) sites, dieldrin declined from 1.0 μg/g in 1975 to 0.82 μg/g in 1977-1978, 0.69 μg/g in 1990, and 0.03 μg/g in 2002, suggesting that, following a steady but slow decline in the 1970s and 1980s, a more rapid decline took place in the 1990s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1975, White and Cromartie (1977) analyzed 18 red-breasted merganser eggs from the same area in Lake Michigan as we collected from; the mean concentration of PCBs was 45 μg/g, compared to 21 μg/g in our 1977-1978 collection, 8.5 μg/g in our 1990 collection, and 4.6 μg/g in our 2002 collection. The White and Cromartie (1977) means were arithmetic means, but according to White (personal communication) the arithmetic and geometric means were very Table 1 Comparison of organochlorine pesticides and PCBs (μg/g, wet-weight; n = 12) in red-breasted merganser eggs collected in 1977-1978, 1990, and 2002from Lake Michigan 1977-197819902002 PCBs 21 a (10-34) b A 8.5 (4.0-14) B 4.6 (1.8-13) C p, p -DDE 6.5 (3.3-11) A 2. 2 (1.1-3.3 Faber and Hickey (1973), and the 1975 data came from White and Cromartie (1977) sites, dieldrin declined from 1.0 μg/g in 1975 to 0.82 μg/g in 1977-1978, 0.69 μg/g in 1990, and 0.03 μg/g in 2002, suggesting that, following a steady but slow decline in the 1970s and 1980s, a more rapid decline took place in the 1990s.…”
Section: Resultsmentioning
confidence: 99%
“…Contaminants were suspected as the cause of impaired reproduction of bald eagles (Haliaeetus leucocephalus) in Lake Superior (Kozie and Anderson 1991), Forster's terns (Sterna forsteri) from Lake Michigan (Kubiak et al 1989), and double-crested cormorants from Lake Michigan and other Great Lakes (Tillitt et al 1992). Weseloh et al (2002) concluded that DDE, PCBs, and possibly mirex, at levels estimated to be in bald eagle eggs in 1993 and 1994 in certain parts of the Great Lakes, might still be having an adverse impact on productivity. Continued monitoring of contaminant burdens and reproductive success is still needed for the more sensitive species of fish-eating birds.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, migratory birds are of conservation interest because of the essential roles they play in ecosystems, their cultural appeal and symbolic importance, and because population declines have been observed on local to global scales (Cury et al 2011, Rosenberg et al 2019. Avian species have additionally served as indicators of ecosystem health in conservation and restoration projects worldwide (Weseloh et al 2002, Frederick et al 2009, Scopel et al 2018, Velarde et al 2019. Despite these values, gulls (Larus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…They also induce the monooxygenase enzymes [13] and have been associated with fish diseases [14], endocrine and reproductive changes [15], and immunosuppressive effects [16]. Despite nationally declining trends, there is potential for remaining organochlorine residues to adversely affect aquatic life and wildlife, especially given the uncertainty in thresholds for adverse effects [17,18]. Organochlorine pesticides were widely detected in fish and sediment from U.S. streams during the 1990s, and concentrations in some areas were high compared with environmental benchmarks [2] ( Supporting Information Table S1; ).…”
Section: Introductionmentioning
confidence: 99%